2002
DOI: 10.1002/humu.10126
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novelCYP2A7/CYP2A6 hybrid allele (CYP2A6*12) that causes reduced CYP2A6 activity

Abstract: The human CYP2A6 enzyme metabolizes certain drugs and pre-carcinogens and appears to be the most important enzyme for nicotine metabolism. At present, more than 10 different allelic variants are known that cause abolished or decreased enzyme activity. Genetic polymorphism in this gene might be of particular importance for an individual's need for nicotine and for susceptibility to lung and/or liver cancer. We have identified a new CYP2A6 allele (CYP2A6*12) which carries an unequal crossover between the CYP2A6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
80
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 34 publications
5
80
0
3
Order By: Relevance
“…33,34 We investigated four CYP2A6 genetic variants, CYP2A6*2, CYP2A6*4, CYP2A6*9A and CYP2A6* 12A, which are common among Caucasians, 15 and have a known detrimental impact on enzyme function. 4,11,[35][36][37] To assess whether CYP2A6 genetic variants affect enzyme activity, smoking behaviours and plasma levels from treatments, CYP2A6 activity groups were defined based on the impact of each CYP2A6 allele. 8,11,35,[37][38][39] Thus, our study aimed to assess the impact of CYP2A6 genotypes on: (1) CYP2A6 activity using the 3HC/COT ratio derived from baseline smoking, (2) on pre-treatment baseline smoking behaviour in a treatment-seeking group and (3) on usage of nicotine patch and spray and resultant plasma nicotine and cotinine levels obtained.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 We investigated four CYP2A6 genetic variants, CYP2A6*2, CYP2A6*4, CYP2A6*9A and CYP2A6* 12A, which are common among Caucasians, 15 and have a known detrimental impact on enzyme function. 4,11,[35][36][37] To assess whether CYP2A6 genetic variants affect enzyme activity, smoking behaviours and plasma levels from treatments, CYP2A6 activity groups were defined based on the impact of each CYP2A6 allele. 8,11,35,[37][38][39] Thus, our study aimed to assess the impact of CYP2A6 genotypes on: (1) CYP2A6 activity using the 3HC/COT ratio derived from baseline smoking, (2) on pre-treatment baseline smoking behaviour in a treatment-seeking group and (3) on usage of nicotine patch and spray and resultant plasma nicotine and cotinine levels obtained.…”
Section: Introductionmentioning
confidence: 99%
“…12 The CYP2A6*12 is a CYP2A7/CYP2A6 hybrid allele created by an unequal crossover in intron 2. 13 Recently, we developed a genotyping method to distinguish the CYP2A6*4A, CYP2A6*4D, CYP2A6*1F, and CY-P2A6*1G alleles. 14 Using this method, we found that 14 out of 187 European-American subjects heterozygously possessed the CYP2A6*4A allele, resulting in an allele frequency of 3.7%.…”
Section: Introductionmentioning
confidence: 99%
“…90% in other populations studied to date. [19][20][21][22] The second purpose of this study was to investigate whether CYP2A6 polymorphisms are associated with individual susceptibility to smoking dependence.…”
Section: Introductionmentioning
confidence: 99%